Developing Manipulative Basic Movement Learning Model Based on Traditional Games in Elementary Schools - Hendriana Sri Rejeki; Humaedi Humaedi; A. Ardiansyah (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This study aims to develop manipulative basic movement learning models based on tradition games at Elementary schools. Research and development method adopted from Borg and Gall was used. The effectiveness of the application of the manipulative basic motion learning model and catch and capture in these students used the